Genetic polymorphisms and the impact of a higher clopidogrel dose regimen on active metabolite exposure and antiplatelet response in healthy subjects - Simon, T; Bhatt, D L; Bergougnan, L; Farenc, C; Pearson, K; Perrin, L; Vicaut, E; Lacreta, F; Hurbin, F; Dubar, M (Clinical pharmacology and therapeutics, 2011)
A double-blind crossover study was conducted in four CYP2C19 genotype-defined metabolizer groups to assess whether increase in clopidogrel dosing can overcome reduced pharmacodynamic response in CYP2C19 poor metabolizers (PMs). Ten healthy subjects in each of four metabolizer groups were randomized to a clopidogrel regimen of a 300-mg loading dose (LD) and a 75-mg/day maintenance dose (MD) for 4 days followed by 600-mg LD and 150 mg/day MD, or vice versa. The exposure levels of clopidogrel's active metabolite H4 (clopi-H4) in PMs were 71% lower on the 75-mg/day regimen and 64% lower on the 150-mg/day regimen than the corresponding exposure levels in extensive metabolizers (EMs). In PMs, the maximal platelet aggregation (MPA) induced by adenosine diphosphate (ADP) 5 µmol/l was 10.5% lower on the 75-mg/day regimen and 7.9% lower on the 150-mg/day regimen than the corresponding values in EMs. PMs who were on the clopidogrel regimen of 600-mg LD/150 mg/day MD showed clopi-H4 exposure and MPA levels similar to those in EMs who were on the regimen of 300-mg LD/75 mg/day MD. In a pooled analysis evaluating CYP1A2, CYP2B6, CYP2C9, CYP2C19, CYP3A5, CYP2D6, ABCB1, and P2RY12 polymorphisms (N = 396 healthy subjects), only CYP2C19 had a significant impact on antiplatelet response. In healthy CYP2C19 PMs, a clopidogrel regimen of 600-mg LD/150 mg/day MD largely overcomes diminished clopi-H4 exposure and antiplatelet response, as assessed by MPA levels.